Unstable familial translocations: A t(11;22)mat inherited as a t(11;15). - Tomkins, D J (1981)
Unusual inheritance of a reciprocal translocation, t(11;22)(p11;p12)mat was discovered in a family with one daughter having a different translocation, t(11;15)(p11;p12). Another daughter inherited the same translocation as her mother. The breakpoints through the nucleolar organizing regions (NORs) of chromosomes 15 and 22 were determined by silver staining. A review of the literature has demonstrated that such unstable familial translocations are very rare and can occur either in mitosis or meiosis. They usually involve exchanges between centromeres, telomeres, or NORs.